Effects of cipepofol on breathing patterns, respiratory drive, and inspiratory effort in mechanically ventilated patients - Su, Rui; Zhang, Linlin; Wang, Yu-Mei; Miao, Ming-Yue; Wang, Shuya; Cao, Yong; Zhou, Jian-Xin (Frontiers in Medicine, 2025)
BackgroundCipepofol is a highly selective gamma-aminobutyric acid A receptor potentiator. As a new sedative drug, detailed studies on its respiratory effects are further needed. The present study aims to investigate the effects of cipepofol on breathing patterns, respiratory drive, and inspiratory effort in mechanically ventilated patients.MethodsIn this one-arm physiological study, cipepofol was initiated at 0.3 mg/kg/h and increased by 0.1 mg/kg/h every 30 min until reaching 0.8 mg/kg/h. Discontinuation criteria were Richmond Agitation and Sedation Scale (RASS) score ≤ −4 or respiratory rate (RR) < 8 breaths/min or pulse oxygen saturation (SpO2) < 90%. The primary outcomes were changes from baseline in respiratory variables [RR, tidal volume (VT), minute ventilation (Vmin), airway occlusion pressure at 100 msec (P0.1), pressure muscle index (PMI), expiratory occlusion pressure (Pocc)] at 30 min after 0.3 mg/kg/h cipepofol infusion. The secondary outcomes included changes in respiratory variables, cardiorespiratory variables, and RASS scores at rates of cipepofol from 0.3 to 0.8 mg/kg/h.Results20 patients were enrolled and all of them completed the cipepofol infusion rate at 0.3 mg/kg/h, achieving RASS score of −2 to +1. For the primary outcomes, there was a significant reduction in VT (390.9, [356.6–511.0] vs. 451.6 [393.5–565.9], p = 0.002), while changes in RR (16.7 ± 2.7 vs. 16.2 ± 3.4, p = 0.465) and Vmin (7.2 ± 1.8 vs. 7.5 ± 1.9, p = 0.154) were not significant. The reductions in P0.1 (p = 0.020), PMI (p = 0.019), and Pocc (p = 0.007) were significant. For secondary outcomes, as the infusion rate of cipepofol increased from 0.3 to 0.8 mg/kg/h, there was a further decrease in VT (p = 0.002) and an increase in RR (p < 0.001), while the change in Vmin (p = 0.430) was not significant. RASS score (p < 0.001) was further decreased.ConclusionCipepofol demonstrates the capability to achieve RASS score −2 to +1 in mechanically ventilated adult patients. The effect of cipepofol on breathing patterns was a decrease in VT, while changes in RR and Vmin were insignificant. The effect on respiratory drive and inspiratory effort significantly reduced P0.1, PMI, and Pocc.Clinical trial registrationClinicalTrials.gov, identifier NCT06287138. https://clinicaltrials.gov/study/NCT06287138